Al2O3 Underlayer Prepared by Atomic Layer Deposition for Efficient Perovskite Solar Cells. Issue 19 (21st September 2017) - Zhang, Jinbao; Hultqvist, Adam; Zhang, Tian; Jiang, Liangcong; Ruan, Changqing; Yang, Li; Cheng, Yibing; Edoff, Marika; Johansson, Erik M. J.
Abstract: Perovskite solar cells, as an emergent technology for solar energy conversion, have attracted much attention in the solar cell community by demonstrating impressive enhancement in power conversion efficiencies. However, the high temperature and manually processed TiO2 underlayer prepared by spray pyrolysis significantly limit the large‐scale application and device reproducibility of perovskite solar cells. In this study, lowtemperature atomic layer deposition (ALD) is used to prepare a compact Al2 O3 underlayer for perovskite solar cells. The thickness of the Al2 O3 layer can be controlled well by adjusting the deposition cycles during the ALD process. An optimal Al2 O3 layer effectively blocks electron recombination at the perovskite/fluorine‐doped tin oxide interface and sufficiently transports electrons through tunneling. Perovskite solar cells fabricated with an Al2 O3 layer demonstrated a highest efficiency of 16.2 % for the sample with 50 ALD cycles (ca. 5 nm), which is a significant improvement over underlayer‐free PSCs, which have a maximum efficiency of 11.0 %. Detailed characterization confirms that the thickness of the Al2 O3 underlayer significantly influences the charge transfer resistance and electron recombination processes in the devices. Furthermore, this work shows the feasibility of using a high band‐gap semiconductor such as Al2 O3 as the underlayer in perovskite solar cells and opens up pathways to use ALD Al2 O3 underlayers for flexible solar cells. Abstract : Tunneling through the underlayer ! Atomic layer deposition (ALD) is used to prepare a compact Al2 O3 underlayer for perovskite solar cells. The thickness of the Al2 O3 layer can be controlled well by adjusting the deposition cycles during the ALD process. The Al2 O3 layer can effectively block electron recombination at the perovskite/fluorine‐doped tin oxide interface and can sufficiently transport the electrons through tunneling.